Decision making : 5 steps to better results - Luecke, Richard; Harvard Business School (Boston, Mass. : Harvard Business School Press, 2006)
"Decision making is a critical part of management, and bad choices can damage careers and the bottom line. This book offers the tools and advice managers need to avoid common biases and arrive at and implement decisions that are both sound and ethical.The Harvard Business Essentials series provides comprehensive advice, personal coaching, background information, and guidance on the most relevant topics in business. Whether you are a new manager seeking to expand your skills or a seasoned professional looking to broaden your knowledge base, these solution-oriented books put reliable answers at your fingertips."--EBSCO.
The decision process : five key steps -- The context for success : setting the stage -- The framing challenge : what is the real problem? -- Alternatives : the source of superior solutions -- Evaluate the alternatives : finding the value of each option -- Make the decision : getting to agreement -- The uncertainty problem : and how to deal with it -- Human foibles : waiting to ambush your decision -- Organizational traps : the madness and the wisdom of crowds -- Toward a smarter organization : getting better at making decisions.
Includes bibliographical references and index.
Online resource; title from title screen (viewed October 7, 2021).
WorldCat record variable field(s) change: 650
Keywords: Decision making; Management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Decision making; elektronické knihy; electronic books